2010
DOI: 10.1590/s1676-06032010000100029
|View full text |Cite
|
Sign up to set email alerts
|

Microestrutura de pêlos-guarda de felídeos Brasileiros: considerações para a identificação de espécies

Abstract: VANSTREELS, R.E.T., RAMALHO, F.P. &ADANIA, C.H. Guard-hair microstructure of Brazilian felids: considerations for species identification. Biota Neotrop.10(1): http://www.biotaneotropica.org.br/v10n1/en/ abstract?article+bn00910012010. Abstract:The analysis of cuticle and medulla hair microstructure is a simple and inexpensive technique to identify mammal species for a variety of applications. We studied the guard-hairs of 66 individuals of eight felid species occurring in Brazil (Leopardus colocolo, L.geoffroy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
(13 reference statements)
1
13
0
5
Order By: Relevance
“…We cleaned the guard hairs with ethyl alcohol, and the cuticular impressions were obtained by pressing the hairs against a thin layer of nail varnish and leaving them to dry for three to five minutes on glass slides with the help of a bench vise (adapted from [65]). We photographed the cuticular impressions at 400x magnification (S2 Fig) and compared the pattern of the cuticles with our reference collection (obtained from hairs collected from museum specimens) and published guides [66, 67]. …”
Section: Methodsmentioning
confidence: 99%
“…We cleaned the guard hairs with ethyl alcohol, and the cuticular impressions were obtained by pressing the hairs against a thin layer of nail varnish and leaving them to dry for three to five minutes on glass slides with the help of a bench vise (adapted from [65]). We photographed the cuticular impressions at 400x magnification (S2 Fig) and compared the pattern of the cuticles with our reference collection (obtained from hairs collected from museum specimens) and published guides [66, 67]. …”
Section: Methodsmentioning
confidence: 99%
“…The development of the two layers varies with the climate of the environment where the animal is found; it also underwent modifications due to the domestication process (Dreyer, 1966). The undercoat is shorter, thinner, wavy and numerous, it contributes to thermoregulation and protects against water penetration (Vanstreels et al, 2010). The guard coat is longer, thicker and less numerous, it stands out and contributes mainly to mechanoreception, camouflage in the environment and general pattern determination of coat coloration (Teerink, 1991;Martin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This technique, however, is not without shortcomings. The results obtained illustrate that spe- cific determination by visual comparison of scale widths (QUADROS & MONTEIRO-FILHO 2010, VANSTREELS et al 2010) is subjective and cannot be used to identify the species of these small Neotropical felids, even with the use of metric variables (see the overlap of metrics of hair scales in Figs. 7 and 8).…”
mentioning
confidence: 97%
“…In a study that included all Brazilian felid species, VANSTREELS et al (2010) indicated that they were able to successfully identify only 75% of the samples. Because this indirect tool is so important and so widely used (e.g., WANG 2002, MARTINS et al 2008, TÓFOLI et al 2009, BIANCHI et al 2011, SILVA-PEREIRA et al 2011, and considering the flaws in the diagnostics elaborated by VANSTREELS et al (2010) (their method is circular: they used only qualitative characters for species determination, which in turn are dependent on the experience and the skills of the observer), we endeavored to evaluate metrically its usefulness to identify L. guttulus, P. yagouaroundi, L. wiedii, and L. pardalis.…”
mentioning
confidence: 99%
See 1 more Smart Citation